Analisis Yuridis Terhadap Penyelesaian Sengketa Merek Gudang Garam Dan Gudang Baru (Studi Kasus Putusan Nomor 104 PK/Pid.Sus/2015) - Muhamad Ikbal Hajizi; Mohammad Ali Wafa; Muhammad Yasir (JOURNAL of LEGAL RESEARCH, 2019)
Abstract:Provisions regarding the resolution of trademark disputes in CHAPTER XV of Law Number 20 Year 2016 concerning Trademarks and Geographical Indications state that the procedure for resolving trademark disputes can be carried out in civil cases through the Commercial Court within the scope of General Courts/District Courts, Crimes through District Courts, Arbitration through Arbitration Institutions, and Other alternative dispute resolution in accordance with the agreement of the parties to the dispute. The existence of provisions regarding civil and criminal settlement in trademark problems sometimes causes polemic, because in the legal world the boundary between criminal law and civil law is very thin. Therefore, it is not uncommon in trademark disputes that should be resolved by civil law instead ends with criminal sanctions. The purpose of this study is to find out the procedure for resolving trademark disputes if resolved in a Civil and criminal manner, as well as the causes of Dissenting Opinion of the Supreme Court judges in examining the Review of the New Gudang brand in decision No. 104 PK/ Pid.Sus / 2015.Keywords: Brand Dispute Resolution, Dissenting Opinion